The Economic Importance of Art and Craft: Men as Artisans at Ranchi Cluster in Jharkhand State - Ashish Prasad (Recent Trends in Social Studies, 2024)
There is an inseparable relationship between Art, culture and civilization in India. As man Gradually developed, art also kept on developing along with his civilization. Be it the civilization of any country. Its emergence has been the result of human imagination. Art has always had a significant historical significance, transcended cultural borders and acted as a monument to humanity's inventiveness and imagination. Artists have risen throughout history as guardians of culture, maintaining traditions and bringing beauty into the world. The Study investigates the significant economic contributions of male artisans and their creative endeavors within the larger economy. It’s also dives into the diverse contributions made by male craft workers and their significant economic influence through their artistic activities. Researcher investigates the wide range of creative fields in which male artisans thrive, as well as the economic ramifications of their work. This study examines the entrepreneurial drive, skill development, market expansion, and cultural preservation activities of male craft workers in driving economic growth and cultural development. While they frequently identified female artisans with the creative sector, this research emphasizes the critical role that male artisans play in driving economic growth, supporting cultural preservation, and promoting social development. This study sheds light on the transformational impact of male artisans it examines that why males are turning towards different occupations. It underlines the need for inclusive support and recognition within the creative industry by evaluating the many artistic disciplines and their accompanying economic ramifications.The Story of its development from the emergence of the art is the story of our development. Through which we are doing the work of saving our civilization. So that our future generations can also know the story of its progress.
Keywords: Cultural Preservation; Entrepreneurial Drive; Handicraft; Market Explain; skill development